220k views
4 votes
for In the given​ expression, calculate as indicated. Express your answer as a single polynomial in standard form. 4x^(3)-2x^(2)+9)-(6x^(2)-6x+5), what is the answer

User Rlandster
by
5.5k points

1 Answer

5 votes

Answer:

The polynomial in standard form is
y = 14 + 6\cdot x - 8\cdot x^(2)+4\cdot x^(3).

Explanation:

A polynomial in standard fulfills the following condition:


y = \Sigma_(i=0)^(m)\,c_(i)\cdot x^(i),
\forall\,i\in \mathbb{N},
0 \leq i \leq m

Let be
y = (4\cdot x^(3)-2\cdot x^(2)+9)-(6\cdot x^(2)-6\cdot x + 5), which is now handled algebraically:

1)
(4\cdot x^(3)-2\cdot x^(2)+9)-(6\cdot x^(2)-6\cdot x + 5) Given

2)
(4\cdot x^(3)-2\cdot x^(2)+9) +(-1)\cdot (6\cdot x^(2)-6\cdot x + 5)
(-1)\cdot a = -a

3)
(4\cdot x^(3)-2\cdot x^(2)+9) +[(-1)\cdot (6\cdot x^(2))+(-6\cdot x)\cdot (-1)+5] Definition of substraction/Distributive property

4)
(4\cdot x^(3)-2\cdot x^(2)+9)+(-6\cdot x^(2)+6\cdot x + 5)
(-1)\cdot a = -a/
(-a)\cdot (-b) = a\cdot b

5)
4\cdot x^(3)+ (-2\cdot x^(2)-6\cdot x^(2))+6\cdot x + (9+5) Associative and commutative properties

6)
4\cdot x^(3)-8\cdot x^(2)+6\cdot x + 14 Distributive property/Definition of addition

7)
14 + 6\cdot x -8\cdot x^(2)+4\cdot x^(3) Commutative property/Result

The polynomial in standard form is
y = 14 + 6\cdot x - 8\cdot x^(2)+4\cdot x^(3).

User Isamar
by
6.0k points